A new finite element method framework for axially functionally-graded nanobeam with stress-driven two-phase nonlocal integral model. (1st September 2022) - Bian, Pei-Liang; Qing, Hai; Yu, Tiantang
Abstract: Nano-structures always show size effects. In the paper, a new FEM framework is developed to analyze the mechanical responses of nanobeams made of axially functionally-graded material (FGM) under different boundary conditions. The stress-driven two-phase nonlocal integral model is utilized to introduce the size effect into the model. The present work is based on the nonlocal constitution in a differential form and the corresponding constitutive boundary conditions are converted to external loads equivalently. A series of numerical examples, including static bending, buckling, and free vibration are carried out for the beams with different boundary conditions and various nonlocal and FGM parameters. The present framework shows a promising way for its flexibility in handling complex FGM distribution patterns, boundary conditions, and loads.